The Bankruptcy Rules in Linear Ordered Structures - Muchna, Jan; Pánková, Václava, 1949-; Černý, Michal; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2010)
The bankruptcy problem involves the distribution of perfectly divisible goods. Particular attention is paid to the situations, where the amount of goods available is not enough to cover the demand. An example of real life situations that can be solved using various bankruptcy rules may be a division of a heritage or when a company goes bankrupt and its estates are sold to satisfy interested parties' claims. This paper introduces to the problem a linear structure of the participants, meaning that participants are now satisfied one after another in a preset order. It applies the equal awards (CEA) and the equal losses (CEL) solutions on the revised problem. Since their axiomatization is no longer valid, both solutions are extended and new characterizations are given in the thesis. The thesis contains a series of original proofs for both extended solutions and whole problem is examined in the setting of the well-known river sharing problem.
Vedoucí práce: Václava Pánková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: ekonometrie a operační výzkum [obor dipl. práce]; diplomové práce; master's theses